ANXIETY LEVEL OF MIDWIFERY CLINICAL STUDENTS DURING COVID-19 PANDEMIC - Nadia Sherli Syafira; Muhammad Miftahussurur; Endyka Erye Frety (UNIVERSITAS AIRLANGGA, 2022)
Introduction: Clinical midwifery students experience higher anxiety than the general population during COVID-19 pandemic. The higher level of anxiety is due to pressure in their clinical learning environment. This study will explore the effect of the clinical learning environment on the increased anxiety in midwifery students during the COVID-19 pandemic. Method: This prospective cross-sectional study was conducted on 82 clinical midwifery students at Airlangga University using an online survey. We excluded students who had not started clinical studies and students with pre-existing medical or comorbid psychiatric conditions that could explain the pain. Information from participants included socio-demographic, clinical learning environment questionnaire, and Hamilton Rating Scale for Anxiety (HRS-A). Results: The study showed that most of the respondents aged 20-27 years (73.2%), in the second semester (76.8%), living in boarding houses/contracts (74.4%), unmarried status (75.6%), the level of family income is very high (68.3%), and the perception of a poor clinical learning environment (51.2%). Participants experienced no anxiety the most (52.4%) and significantly correlated with the age p=0.047, domicile status p=0.076, and clinical learning environment p=0.008. But not their semester p=0.991, marital status p = 0.406, and family income p=0.872. Conclusion: These data indicate that age, domicile status, and clinical learning environment contribute to the incidence of anxiety in midwifery clinic students during the COVID-19 pandemic.